2003
DOI: 10.1111/j.1552-6569.2003.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and Systemic Hemodynamics Changes During Upright Tilt in Chronic Fatigue Syndrome

Abstract: The results of this study are not consistent with the hypothesis that patients with CFS have a distinctive pattern of MCA CBFV changes in response to orthostatic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…First, contrary to our hypothesis, patients with POTS did not have impaired cerebral perfusion compared with normal control subjects, despite the presence of a cardiovascular profile during HUT, suggestive of increased orthostatic stress. In this regard, our data confirm the observations of others who did not observe reductions in CBV during orthostatic stress in POTS (22,38) and are not consistent with other studies in which CBV was excessively reduced during HUT (23,34).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…First, contrary to our hypothesis, patients with POTS did not have impaired cerebral perfusion compared with normal control subjects, despite the presence of a cardiovascular profile during HUT, suggestive of increased orthostatic stress. In this regard, our data confirm the observations of others who did not observe reductions in CBV during orthostatic stress in POTS (22,38) and are not consistent with other studies in which CBV was excessively reduced during HUT (23,34).…”
Section: Discussionsupporting
confidence: 65%
“…The changes in cerebral perfusion during standing in patients with POTS have been measured using transcranial Doppler sonography of the middle cerebral artery (MCA). Some investigators did find that MCA cerebral blood velocity (CBV) decreased excessively during orthostatic stress (23,34), whereas others found no such change in CBV, despite the presence of symptoms suggestive of cerebral hypoperfusion (22,38). The reduction in CBV during orthostatic stress has been attributed to excessive hyperventilation (34) or to exaggerated sympathetic activity directed to cerebral vasculature (28).…”
mentioning
confidence: 99%
“…However, work by Fischler et al [27] and MacHale et al [28] could not confirm any deficits in CFS cerebral perfusion. Additionally, a study by Rowe and co-workers [29] using transcranial Doppler sonography did not find any differences in CBFV (cerebral blood flow velocity) between CFS and control subjects during upright tilt. The results of these measurements of cerebral perfusion in CFS/POTS are controversial, and these differences may be methodological.…”
Section: Introductionmentioning
confidence: 91%
“…16 While these perfusion deficits are either absent or different in comorbid illnesses such as depression, 21, 22 not all studies have identified neural perfusion abnormalities in CFS. 23 Also, like the MRI methodologies, the detection of these abnormalities may be expensive and difficult to implement. Continued research into the presence of perfusion abnormalities in a subset of patients with CFS may be useful in characterizing a neurological subtype of the illness, and in developing treatment strategies (e.g., increasing blood volume to restore cerebral perfusion).…”
Section: Neurological Biomarkers Of Cfs (Table 1)mentioning
confidence: 99%
“…In the neurological domain, many of these biomarkers lack specificity for CFS, are highly varied between patients with CFS, or require technological methods whose expense and complexity limit practical clinical application (e.g., fMRI). 23 In the immunological domain, diurnal variations in inflammatory markers make it difficult to draw cause-effect conclusions and create quantitative parameters for prognostic evaluation. 39 Differences in results may be, at least in some reports, attributed to total or partial differences in methodologies.…”
Section: A Critical Review Of Biomarkers For Cfs: Limitations and Futmentioning
confidence: 99%